2008
DOI: 10.1111/j.1537-2995.2008.01825.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of donor deferrals for malaria on blood availability in the United States

Abstract: The vast majority of malaria deferrals were for travel to endemic areas; however, few US donors visit those areas associated with most US cases of malaria or transfusion-transmitted malaria. Current interventions fail to capture many semi-immune donors, those at greatest risk for transmitting infection. Considerations should be given to selective screening and permanent deferral of donors with a history of malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 17 publications
0
44
0
Order By: Relevance
“…Such models are useful for the evaluation of antigen immunoreactivity during the acute and chronic phases of infection. Current U.S. blood donor evaluation policy results in deferral of 73,000 to 75,000 donations per year due to travel, residence in an area where malaria is endemic, or a history of malaria (28,29). Implementation of universal donor screening, or screening of deferred donors for reentry into the donation a Data represent EIA results obtained using beads cocoated with four MSP1-p19 recombinant proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such models are useful for the evaluation of antigen immunoreactivity during the acute and chronic phases of infection. Current U.S. blood donor evaluation policy results in deferral of 73,000 to 75,000 donations per year due to travel, residence in an area where malaria is endemic, or a history of malaria (28,29). Implementation of universal donor screening, or screening of deferred donors for reentry into the donation a Data represent EIA results obtained using beads cocoated with four MSP1-p19 recombinant proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of donor deferral programs has previously been questioned (29), and there is concern that many donors are needlessly deferred, since the rates of imported malaria are much lower than the rates of travel to areas of endemicity (17,35). To prevent erosion of qualified donor populations, some countries have implemented antibody screening such that only individuals who are known to have been exposed to organisms causing malaria are subject to deferral of donations rather than all donors who have traveled to or lived in regions where malaria is endemic.…”
mentioning
confidence: 99%
“…At the 26 July 2010 meeting of the FDA's Blood Product Advisory Committee, the committee voted unanimously to recommend that if the screening of blood donors for B. microti is implemented, it would be appropriate to screen regionally in areas of high endemicity, but the committee did not provide guidance on which regions should be included or the format of a screening test (1). Donors who visit these regions and become infected by B. microti, only to return to areas where the parasite is not endemic, would be missed, and without universal screening, there is no way to identify these donors short of obtaining a travel history, which is not desirable based on the current blood bank experience with malaria deferral criteria (79). Thus, regionalized testing appears to be the most cost-effective approach from a blood safety, blood availability, and cost structure standpoint; however, final analysis will be dependent upon the cost of the test and licensure by the FDA.…”
Section: Implementation and Cost-benefitmentioning
confidence: 99%
“…Other Plasmodium species occasionally reported as a cause of malaria include; P. ovale, P. malariae and P. knowlesi (Cox-Singh et al, 2008). Although primarily limited to tropical and subtropical regions, cases of malaria are increasingly detected in non endemic areas among travelers and immigrants (Thwing et al, 2007;Leiby et al, 2008). In tropical areas, the parasite is transmitted mainly by the bite of some species of female Anopheles mosquito in addition to transfusion transmitted malaria especially with P. falciparum.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) in 2014 reported that malaria lead to 197 million cases and 584 thousand deaths during 2013 while in 2014, there were an estimated 214 million cases and an estimated 438 thousand deaths (WHO, 2014;2015). Most of malaria deaths occur in sub-Saharan Africa, in children (under 5 years) infected with Plasmodium falciparum (Cox-Singh et al, 2008;Leiby et al, 2008). Falciparum malaria is the commonest cause of severe malaria while vivax malaria may lead to severe anaemia in children.…”
Section: Introductionmentioning
confidence: 99%